MORAL EKONOMI PETANI TOMAT DI RUMBIA JENEPONTO - Muhammad Arman Akil (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2019)
This study aims to determine: (1) Good tomato management process in Tompobulu Village, Rumbia District, Jeneponto Regency, (2) Role of tomato farmers in improving their economic life in Tompobulu Village, Rumbia District, Jeneponto Regency, (3) How to grow tomato farmers in Tompobulu Village, Rumbia District, Jeneponto Regency in managing the economy. In this study used a type of qualitative research that was analyzed and written descriptively. Data collection techniques were carried out using the method of observation, interviews, and documentation involving 9 (nine) informants. Based on the results of the study showed that: (1) How to manage tomatoes that are good in Tompobulu Village is that most of the tomato farmers in the village are two fundamental differences between the past and present in the process of growing the tomato plants, if the farmers used only the inner leaves the nursery process, but now more farmers use plastic bags because they are considered more effective in the nursery process. (2) The role of farmers in Tompobulu village in improving their economy is the tomato farmers' main income because tomatoes are considered the most appropriate commodity because they have a high selling price in the market, but they don't stop at tomato farming alone, they also work on other farms to take advantage of long harvest waiting times so things are done to improve the level of their own economy usually besides planting tomatoes brands a also planting other crops as mentioned by several informants who interviewed researchers such as Sop, Carrots, Chili, Lombok, Coles and Corn. (3) The way the tomato farmers manage their economy is to be dealt with and make a living just for their daily needs, usually they always buy their needs at the beginning with a large amount so that the momentum can be fulfilled for a long period of time.